THE HISTORY OF THE TERM "INFORMATION AND COMMUNICATION COMPETENCE" (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
The development of society and its transition to the information category determines the need to consider historical and international experience on the problem of information and communication competence formation